2019
DOI: 10.1002/cssc.201900226
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Trace Yb Doping on the Electrochemical Performance of Li‐Rich Layered Oxides

Abstract: Layered lithium‐rich cathode materials are one of the most promising cathode materials owing to their higher mass energy density than the commercial counterparts. A series of trace Yb‐doped lithium‐rich cathode materials Li1.2Mn0.54Ni0.13Co0.13−xYbxO2 (0≤x≤0.050) were synthesized and the effects were investigated by XRD, X‐ray photoelectron spectroscopy, and high‐resolution TEM. The participation of Yb ions in electrochemical reactions and the larger binding energy of Yb−O than M−O (M=Mn, Ni, Co), which expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…The rare earth (RE) doping engineering is an effective approach to achieve the uniform distribution of oxygen vacancies from the interior of MoO 3 to the exterior surface, modify the electronic structure, and enlarge layer spacing as well as build Mo‐◌‐RE asymmetric sites as highly active redox sites, [ 23 ] which will significantly enhance conductivity, ion transport channel, and electrochemical activity. [ 24–26 ] Different from the transition metal elements, the RE element has a special outer layer 4f electronic structure, large ion radius, low electronegativity, etc. Therefore, RE doping can greatly affect the electronic structure of the material and endow materials with new properties.…”
Section: Introductionmentioning
confidence: 99%
“…The rare earth (RE) doping engineering is an effective approach to achieve the uniform distribution of oxygen vacancies from the interior of MoO 3 to the exterior surface, modify the electronic structure, and enlarge layer spacing as well as build Mo‐◌‐RE asymmetric sites as highly active redox sites, [ 23 ] which will significantly enhance conductivity, ion transport channel, and electrochemical activity. [ 24–26 ] Different from the transition metal elements, the RE element has a special outer layer 4f electronic structure, large ion radius, low electronegativity, etc. Therefore, RE doping can greatly affect the electronic structure of the material and endow materials with new properties.…”
Section: Introductionmentioning
confidence: 99%
“…In another strategy, cation doping (Al, Mg, Zr, La, Cr, etc.) was explored to stabilize the bulk lattice structure and increase the Li + kinetics, thereby reducing the voltage fading. Meanwhile, particle size reduction was also investigated to enhance the rate capability, which could improve the electronic and ionic conductivity. , …”
Section: Introductionmentioning
confidence: 99%
“…Regarding substitution with ions of a large radius, some studies have shown that an impurity phase may occur when the substitution concentration is too high . For example, substitution elements aggregate on the surface of the material to form oxides . In XRD results, the (003) peak does not show a significant left shift when the substitution amount is x = 0.047 in comparison with x = 0.029 (Figure (c)), indicating that there may be impurities, such as sodium oxide, when the substitution amount is too large.…”
Section: Results and Discussionmentioning
confidence: 65%
“…Some researchers believe that the oxidation of anions in the charging process will lead to generation of O 2 and defects. Once the oxygen evolution occurs, the process is irreversible . However, some studies believe that the redox of anions in some materials is reversible.…”
Section: Results and Discussionmentioning
confidence: 77%